Market Orientation of Moroccan SME Managers and Performance: Does Innovation Capability Matter? - Allammari , Yassin; boujaddaine , Ouiam; Taqi, Ahmed (Journal of Ecohumanism, 2025)
Although previous studies have established a positive relationship between market orientation (MO), innovation capabilities (IC), and SME performance, the specific context of Moroccan SMEs remains underexplored. This study aims to examine how MO and IC interact to enhance the performance of Moroccan SMEs. A quantitative survey was conducted among 84 SME managers operating in various sectors. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via SmartPLS 4. The results indicate that MO has a positive and direct effect on the performance of Moroccan SMEs. Additionally, IC play a partial mediating role in this relationship. The theoretical and practical implications of these findings provide concrete guidance for SME managers and policymakers, highlighting the strategic importance of strengthening MO and enhancing IC to foster sustainable SME performance in Morocco.